Study protocol for a self-controlled cluster randomised trial of the Alert Program to improve self-regulation and executive function in Australian Aboriginal children with fetal alcohol spectrum disorder. Issue 3 (25th March 2018) - Wagner, Bree; Fitzpatrick, James P; Mazzucchelli, Trevor G; Symons, Martyn; Carmichael Olson, Heather; Jirikowic, Tracy; Cross, Donna; Wright, Edie; Adams, Emma; Carter, Maureen; Bruce, Kaashifah; Latimer, Jane
Abstract : Introduction: While research highlights the benefits of early diagnosis and intervention for children with fetal alcohol spectrum disorders (FASD), there are limited data documenting effective interventions for Australian children living in remote communities. Methods and analysis: This self-controlled cluster randomised trial is evaluating the effectiveness of an 8-week Alert Program school curriculum for improving self-regulation and executive function in children living in remote Australian Aboriginal communities. Children in grades 1–6 attending any of the eight participating schools across the Fitzroy Valley in remote North-West Australia ( N ≈ 363) were invited to participate. Each school was assigned to one of four clusters with clusters randomly assigned to receive the intervention at one of four time points. Clusters two, three and four had extended control conditions where students received regular schooling before later receiving the intervention. Trained classroom teachers delivered the Alert Program to students in discrete, weekly, 1-hour lessons. Student outcomes were assessed at three time points. For the intervention condition, data collection occurred 2 weeks immediately before and after the intervention, with a follow-up 8 weeks later. For control conditions in clusters two to four, the control data collection matched that of the data collection for the intervention condition in the preceding cluster. The primary outcome is change in self-regulation. FASD diagnoses will be determined via medical record review after the completion of data collection. The results will be analysed using generalised linear mixed modelling and reported in accordance with Consolidated Standards of Reporting Trials (CONSORT) guidelines. Ethics and dissemination: Ethical approval was obtained from the University of Western Australia (WA) (RA/4/1/7234), WA Aboriginal Health Ethics Committee (601) and WA Country Health Service (2015:04). The Kimberley Aboriginal Health Planning Forum Research Sub-Committee and WA Department of Education also provided approval. The results will be disseminated through peer-reviewed journals, conference presentations, the media and at forums. Trial registration number: ACTRN12615000733572; Pre-results.